2013
DOI: 10.1007/s10869-013-9334-5
|View full text |Cite
|
Sign up to set email alerts
|

Building and Sustaining Proactive Behaviors: The Role of Adaptivity and Job Satisfaction

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
(83 reference statements)
2
32
0
2
Order By: Relevance
“…Johnson and McIntye [30] believe that engagement and devotion towards a company are dependent on the degree of satisfaction at the work place which includes: safety of the work place, the salary, additional benefits, training and taking part in the decision making process. These findings have been confirmed by many other studies, among which: [30][31][32][33][34]. Latham [34], considers that the relationship between work achievement and satisfaction is a reciprocal-conditioned process, and the satisfaction can be the cause and the effect in the same time.…”
Section: Literature Review and Theoretical Frameworksupporting
confidence: 67%
“…Johnson and McIntye [30] believe that engagement and devotion towards a company are dependent on the degree of satisfaction at the work place which includes: safety of the work place, the salary, additional benefits, training and taking part in the decision making process. These findings have been confirmed by many other studies, among which: [30][31][32][33][34]. Latham [34], considers that the relationship between work achievement and satisfaction is a reciprocal-conditioned process, and the satisfaction can be the cause and the effect in the same time.…”
Section: Literature Review and Theoretical Frameworksupporting
confidence: 67%
“…For example, research has demonstrated that job crafting (a type of proactive behaviour) was beneficial for aiding employees to adapt to austerity related changes in Greece (Demerouti et al, ; Petrou, Demerouti, & Xanthopoulou, ). However, due to the lack of available job resources during times of austerity, employees are less likely to engage in effortful proactive behaviour (Strauss, Griffin, Parker, & Mason, ; Strauss, Parker, & O'Shea, ).…”
Section: Proactive Behaviour During Economic Recessionmentioning
confidence: 99%
“…Yao and Wang concerned organizational outcomes of normative commitment in Chinese companies, examined the relationship among employee job satisfaction, in-role performance, and organizational behaviour [14]. Strauss et al claimed that a high level of satisfaction can sustain proactivity [15]. The increasing focus on attitude toward work is linked to the belief that the degree of employee satisfaction is related to various aspects of job behavior, such as productivity, absenteeism, and turnover rates [16].…”
Section: Employee Satisfaction Factors and Commitment To Organizationmentioning
confidence: 99%